Snow in the McMurdo Dry Valleys, Antarctica - Andrew G. Fountain; Thomas H. Nylen; Andrew Monaghan; Hassan J. Basagic; David Bromwich (International Journal of Climatology, 2010)
Snowfall was measured at 11 sites in the McMurdo Dry Valleys to determine its magnitude, its temporal changes, and spatial patterns. Annual values ranged from 3 to 50 mm water equivalent with the highest values nearest the coast and decreasing inland. A particularly strong spatial gradient exists in Taylor Valley, probably resulting from local uplift conditions at the coastal margin and valley topography that limits migration inland. More snow occurs in winter near the coast, whereas inland no seasonal pattern is discernable. This may be due, again, to local uplift conditions, which are common in winter. We find no influence of the distance to the sea ice edge. Katabatic winds play an important role in transporting snow to the valley bottoms and essentially double the precipitation. That much of the snow accumulation sublimates prior to making a hydrologic contribution underscores the notion that the McMurdo Dry Valleys are indeed an extreme polar desert. Copyright © 2009 Royal Meteorological Society